Current climate conditions in the Congo Basin region based on an analysis of temperature data - (:unkn) unknown (My University, 2025)
CURRENT CLIMATE CONDITIONS IN THE CONGO BASIN REGION BASED ON AN ANALYSIS OF TEMPERATURE DATA ABSTRACT : Tropical forests are of real interest to humans. Covering an area of approximately 170 million hectares (36% of the land), they are a source of steam but also carbon sinks [1]. In terms of climate, the distribution of forests plays a fundamental role in the preservation and conservation of biodiversity. They contribute significantly to the regulation of global temperature and seasonal cycles [2]. There is a danger to the environment that essential fauna and flora will disappear irreversibly. In recent years, there has been a notable increase in natural disasters and sea level rise. In addition, there is greater variability in the seasons, disrupting agricultural activities and animal cycles in particular. Finally, rising global temperatures are causing discomfort for populations (especially in hot countries) and the resurgence of certain diseases [3]. However, there continues to be a notable indifference on the part of the scientific community. It has little interest in studying the impacts of climate on forests (including tropical forests), the environment, and humans. Publications on the use of meteorological data for climate studies are rare. This is due, among other things, to problems accessing in situ data [4]. The tropical forests of the Congo Basin are not sufficiently monitored, diagnosed, and predicted for various reasons. Their long-term meteorological data are difficult to obtain. They are rarely updated, lack reliability, and do not exist consecutively beyond ten to twenty years. Data collection in the intertropical zone and Central Africa is complex. There is a lack of spatial and temporal heterogeneity in the measurement networks. The few publications on the temporal characterization of climate change in the Congo Basin region unfortunately do not contribute enough to raising international awareness [4]. We can access meteorological d
Keywords: African Research